2009
DOI: 10.1111/j.1537-2995.2009.02173.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of red blood cell storage and posttransfusion in vivo survival

Abstract: Background-Storage of RBCs is necessary for an adequate blood supply. However, reports have identified potential negative sequelae of transfusing stored RBCs. An animal model would be useful to investigate the pathophysiology of transfusing stored RBCs. However, it has been reported that storage of rat RBCs in CPDA-1 resulted in an unexpected sudden decline in posttransfusion survival. We developed a mouse model of RBC storage and transfusion to assess survival kinetics of mouse RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(158 citation statements)
references
References 16 publications
8
147
1
2
Order By: Relevance
“…24,25,36 Hod et al 37 recently found free iron released from damaged stored RBC to amplify LPS-induced inflammation in a murine transfusion model. Despite differences in RBC purification and storage conditions between our study and the work by Hod and co-workers, 35,37 several findings are consistent. First, the amount of stored RBC we used to prepare RBC-MV was comparable with that used by Hod et al for injection of stored RBC supernatants or hemolysates.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…24,25,36 Hod et al 37 recently found free iron released from damaged stored RBC to amplify LPS-induced inflammation in a murine transfusion model. Despite differences in RBC purification and storage conditions between our study and the work by Hod and co-workers, 35,37 several findings are consistent. First, the amount of stored RBC we used to prepare RBC-MV was comparable with that used by Hod et al for injection of stored RBC supernatants or hemolysates.…”
Section: Discussionsupporting
confidence: 78%
“…This included dextran sedimentation for RBC enrichment and MV purification from RBC aged longer than what is thought to be equivalent to the human maximum storage time of 42 days. 35 These differences might were given 1×10 9 RBC-MV intravenously 15 minutes later, plasma was obtained, and C5a levels (B) and thrombin activity (C) were determined by ELISA and a thrombin assay, respectively, as indicated in Methods in the online-only Data Supplement. Amplification of pulmonary polymorphonuclear cells (PMN) sequestration (D) and systemic inflammation (E) in LPS-primed B6 mice 4 hours after injection of RBC-MV can be reversed by refludan.…”
Section: Discussionmentioning
confidence: 99%
“…mice. 22,23 Gilson et al 24 as well as Hod et al 25 reported that after 14 days of storage in CPDA-1, murine RBCs had an in vivo 24-h RBC recovery of 64% to 65%, which is similar to the data from human RBCs stored for 42 days. 26 Yu et al reproduced the mature model, characterized the biochemical and functional effects, and studied the mechanisms responsible for the adverse effects of transfusing stored RBCs.…”
Section: Discussionsupporting
confidence: 76%
“…49 Recently, a novel mouse model showed that red cell transfusion of aged blood resulted in oxidative stress and inflammatory cytokine secretion in response to macrophage-ingested iron from membraneencapsulated hemoglobin, but not from stroma-free lysate derived from stored red cells. 74 Long-term effects of the intravenous iron preparations will require careful study in relevant clinical settings. 75,76 …”
Section: Intravenous Iron Therapymentioning
confidence: 99%